Fuel for the fire: how emotion deals with the social movement in Hong Kong’s summer of dissent - Tsang, Eileen Yuk-Ha (Deviant behavior, 2023)
Adopting a non-divisive strategy regarding the Anti-Extradition Law Amendment Bill (Anti-ELAB) movement transformed Hong Kong’s social movement activities when they began in February 2019. Although issues surrounding the 2019 summer of dissent have been widely documented, the personal stories of the activists have largely gone unnoticed. Drawing on emotion as a conceptual framework in social movement studies, emotion informs two crucial aspects of the movement. First, emotion helps explain how kinship relations were forged between many social activists even though they were biologically unrelated. Second, emotion was operationally manifested in negative and positive expressions. Not only anger, hatred, and despair but also bonding through devotion, camaraderie, and solidarity to form sisterhood and brotherhood. This article presents the personal experiences of 33 young activists through in-depth interviews, two reflecting focus groups, and participant observation. Activists reported a robust collective identity as Hong Kong youth and protested in support of Hong Kong’s core values and democracy rather than stand by and watch passively, indulging themselves in self-centered, materialistic pursuits. Emotion in the Anti-ELAB movement was developed in three ways: 1) demands for justice and the formation of a collective identity; 2) the formation of strong emotional bonds of brotherhood and sisterhood; 3) the emergence of a diffused, leaderless social movement facilitated by technologies. Thus, the activists’ perspectives enrich the discussion on an important yet underdeveloped area regarding the role of emotion in social movement research.